2022
DOI: 10.3389/fpls.2022.907635
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Shaker K+ Channel Gene Family in Foxtail Millet (Setaria italica) and Their Role in Stress Response

Abstract: Potassium (K+) is one of the indispensable elements in plant growth and development. The Shaker K+ channel protein family is involved in plant K+ uptake and distribution. Foxtail millet (Setaria italica), as an important crop, has strong tolerance and adaptability to abiotic stresses. However, no systematic study focused on the Shaker K+ channel family in foxtail millet. Here, ten Shaker K+ channel genes in foxtail millet were identified and divided into five groups through phylogenetic analysis. Gene structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Based on empirical findings, it has been observed that when a tomato plant experiences stress due to adverse conditions, there is a notable elevation in the concentration of Ca 2+ . This surge in Ca 2+ concentration prompts the activation of calcium channels inside the plant, thereby exerting regulatory control over crucial physiological processes and augmenting the plant’s resilience to adverse circumstances ( Zhang, 2019 ). This study examines the impact of utilizing oyster shell soil conditioner on the growth of tomato seedlings in acidic soil.…”
Section: Discussionmentioning
confidence: 99%
“…Based on empirical findings, it has been observed that when a tomato plant experiences stress due to adverse conditions, there is a notable elevation in the concentration of Ca 2+ . This surge in Ca 2+ concentration prompts the activation of calcium channels inside the plant, thereby exerting regulatory control over crucial physiological processes and augmenting the plant’s resilience to adverse circumstances ( Zhang, 2019 ). This study examines the impact of utilizing oyster shell soil conditioner on the growth of tomato seedlings in acidic soil.…”
Section: Discussionmentioning
confidence: 99%
“…These members typically feature elements, such as the K + channel KAT/AKT, ion transport domain, cyclic nucleotide-binding domain, KHA domain, ankyrin repeats, and voltage-dependent K + channels. Shaker family members have been identified in species including millet [83], soybean [84], sweet potato [85], and cotton [86].…”
Section: Bioinformatics Prediction and Analysismentioning
confidence: 99%